Comparison and Validation of 10 Equations Including a Novel Method for Estimation of LDL-cholesterol in a 168, 212 Asian Population. Issue 14 (April 2016) - Rim, John Hoon; Lee, Yong-ho; Lee, Myung Ha; Kim, Ha Yan; Choi, Jiin; Lee, Byung-Wan; Kang, Eun Seok; Lee, Hyun Chul; Kim, Jeong-Ho; Lee, Sang-Guk; Cha, Bong-Soo
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Low-density lipoprotein cholesterol (LDL-C) is frequently estimated using the empirical Friedewald equation. We compared the accuracy of the novel equation named as the 180-cell method (180-c), which estimates LDL-C using a stratification approach, to those of 9 previously suggested formulas, including the Friedewald equation. We compared the accuracy of 10 equations by calculating intraclass correlation coefficient (ICC) and weighted kappa index in relation to direct LDL-C measurement values. Two independent populations used in the validation were the Severance Hospital LDL-C (SHL) registry (n = 164, 358) and the Korea National Health and Nutrition Examination Survey (KNHANES) 2009 to 2010 (n = 3, 854), each representing the hospital patient population and the general Korean population, respectively. The 180-c and DeLong equations showed the highest ICCs, indicating the best agreement with direct LDL-C measurement. The 180-c and Chen equations showed the highest kappa indices. For the hypertriglyceridemic subpopulation from SHL, the 180-c equation showed the best agreement with direct LDL-C measurement in terms of ICC. We compared the novel 180-c method for LDL-C estimation with 9 previous formulas in a non-US population as the first external validation. The 180-c equation, with Chen equation, appeared to be more accurate than the Friedewald equation. Although the DeLong equation showed better performance in the hypertriglyceridemic subpopulation, the 180-c equation performed appropriately in Asian population.